All are welcome - Penfold, Alexandra; Kaufman, Suzanne (New York : Alfred A. Knopf, 2018)
Illustrations and rhyming text follow a group of children through a day in school where they learn from each other9́s traditions.
Keywords: Stories in rhyme; Schools -- Juvenile fiction; Cultural pluralism -- Juvenile fiction; Stories in rhyme; Schools -- Fiction; Cultural pluralism -- Fiction; Picture books